"PHYSICAL AND REHABILITATION MEDICINE" IS A NEW SPECIALTY IN THE RANGE OF SPECIALTIES. HISTORY, GOALS, AND TASKS - Алексей Алексеевич Марцияш; Елена Васильевна Колмыкова; Наталья Павловна Батурина; Вадим Гельевич Мозес; Кира Борисовна Мозес; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Александр Анатольевич Шапкин; Александр Алексеевич Сашко (Медицина в Кузбассе)
The lecture presents materials for acquainting specialists with one of the priority projects in the field of healthcare «medical rehabilitation», as an organic component of the provision of primary, specialized, including high-tech, medical care. The main provisions of the concept of development of medical rehabilitation, the documents governing the work of medical rehabilitation, the goal, objectives, principles and target indicators are outlined.